Differences in Conventional Learning with E-learning - Muhamad Sholeh (Universal Journal, 2020)
Educational management, also sometimes known as educational administration, is commonly associated with elementary and secondary schools as well as institutes of higher learning like colleges and universities. Education management professionals can also be found working in governmental agencies, private companies, and not-for-profit organizations. Those working in educational management might develop education policy, conduct research, or consult to help evaluate and develop ways to enrich and enhance the educational system at all levels. Most educational management professionals have earned at least a master's degree and many are licensed teachers or principals. To improve a quality education, we need to manage the education system from conventional learning to e-learning, which can provide convenience in educating students, so that independent learning can create innovation and creativities. Learning is basically the process of adding information and abilities, when thinking about what information and competencies are meant by students, then at that moment we should think about what strategies should be done so that all of them can be achieved effectively and efficiently. This is very important for every teacher to understand, because what must be achieved will determine how to achieve it. A teacher is required to master the learning methods that he does will be able to provide added value for his students. If so far the method of learning is done face to face directly (conventional), but in an era of globalization like this requires educators to use methods that are more effective and efficient. This method is then called the online learning method.